Madjelis Ilmu Pengetahuan Indonesia: The Role of National Scientific Institute amidst the Cold War (Paramita: Historical Studies Journal, 2021)
Abstract: After gaining Independence from the Dutch in 1945, Indonesia urged to found its national research institute. Therefore, the government launched Indonesian Science Council (Madjelis Ilmu Pengetahuan Indonesia/MIPI) in 1956. MIPI was established based on Act. No 6/1956 and acted as the highest national scientific institution with research activities covering the natural sciences, cultural and social sciences. Meanwhile, following the Cold War between the Communist (Soviet) Bloc and the Capitalist (US Bloc), the 1950s saw the rise of communism in South East Asia. The situation worried Americans who, under President Eisenhower, were active in fighting against the spread of communist ideology by giving aids to the countries in the region. Using the history of knowledge as the perspective and employing primary sources, namely Bulletin MIPI, Berita MIPI, this article depicts scientific activities conducted by MIPI in rivalries between the Soviet Bloc and US Bloc during The Cold War. Having good American connections, Madjelis Ilmu Pengetahuan Indonesia had proved to be an eminent actor to promote, produce, and distribute scientific knowledge in the countryâ€™s history.Â Abstrak: Setelah memperoleh kemerdekaan dari Belanda pada tahun 1945, Indonesia perlu segera mendirikan lembaga penelitian nasional. Oleh karena itu, pemerintah mendirikan Madjelis Ilmu Pengetahuan Indonesia (MIPI) Indonesia pada tahun 1956. MIPI didirikan berdasarkan Undang-Undang. no 6/1956 dan bertindak sebagai lembaga ilmiah nasional tertinggi dengan kegiatan-kegiatan yang meliputi ilmu alam, budaya dan ilmu sosial. Sementara itu, dekade 1950-an merupakan periode kebangkitan komunisme di Asia Tenggara. Situasi itu membuat pemerintah Amerika khawatir. Di bawah Presiden Eisenhower mereka aktif memerangi penyebaran ideologi komunis dengan memberikan bantuan kepada negara-negara di kawasan itu. Menggunakan sejarah pengetahuan sebagai perspektif dan memanfaatkan sumber-sumber primer yaitu Buletin MIPI, Berita MIPI artikel ini menggambarkan kegiatan ilmiah yang dilakukan oleh MIPI dalam konteks persaingan antara Blok Soviet dan Blok Amerika Serikat dalam periode Perang Dingin. Memiliki koneksi yang baik dengan Amerika Serikat, Madjelis Ilmu Pengetahuan Indonesia pernah menjadi aktor utama dalam mempromosikan, memproduksi dan mendistribusikan pengetahuan ilmiah dalam sejarah negara ini.Â